Comparative study of the use of metaphor in Karakalpak and English literary speech (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article highlights the understanding and appreciation of how metaphors are used in Karakalpak, English languages, It delves into questions such as how metaphors can be used in both languages or , how metaphors are demonstrated in comparative languages.